Development and evaluation of solid control system to optimize drilling performance - Kinif, I. (Penerbit UTM Press, 2016)
The nature of solid content mechanism in drilling fluids directly affects its properties and causes adverse impact on drilling performance. It has rapidly evolved and become a paramount issue over the years because of challenging drilling operations. To control the impact of the drilled solids on drilling fluid properties, solid control system unit must be capable of removing the drilled solids before the re-circulation. Failure to establish good solid control management may end the operation strategy with dilution method. A rigorous analysis of drilled solid effects and its correlation with poor performance of solid control system significantly reflects on the overall rig performance in optimizing drilling operation. This paper presents a study of two different solid control system configuration used in two drilling wells. The study shows that installation of distributor tank reduces mud overflow and brings in flow control stability. Mud rheologies â Plastic viscosity, Yield Point and Low Gravity Solid are considered for the two solid control systems. The results of the new solid control system design are better than the old one. Plastic viscosity, yield point and low gravity solid values improve by 14 , 17 and 25 respectively. These results can be used to check the drilling performance and also in characterization of the solid control system to enhance the drilling mud capabilities. This research shows the need of engineering evaluation in the solid control system to reduce the chances of frequent drilling problems, rig components wear issue and other drilling fluid related hazards. Â© 2016 Penerbit UTM Press. All rights reserved.